The Legend of Princess Mandalika: The Spirit of Gender Struggle in the Sasak Tribe Community on Lombok Island, West Nusa Tenggara - Hidayat, Roch; Sawitri, Sawitri; Saefuddin, Saefuddin; Nursugiharti, Titih; Aryani, Ni (Research Horizon, 2023)
This study explores the legend of Princess Mandalika and its significance as a symbol of gender struggle among the Sasak tribe on Lombok Island, West Nusa Tenggara. Data collection methods include observations, interviews, and document analysis. The study also incorporates data from social media platforms such as YouTube, Tik Tok, and Facebook, which feature the legend of Princess Mandalika in Lombok. The analysis employs hermeneutic techniques to interpret the legend's meaning in the context of gender struggle for Sasak women and utilizes semiotic theory to uncover symbols within the legend. This research is driven by the enduring oral traditions within the Sasak farming community, focusing on the folklore surrounding the legend of Princess Mandalika. The findings suggest that the gender struggle for equality, as portrayed in the Legend of Princess Mandalika, still encounters sociocultural barriers. The story highlights the sacrifices made by Mandalika, a king's daughter, as she chose to preserve her honor and kingdom by sacrificing herself in the sea. This act symbolizes the spirit of the Sasak women's gender struggle to maintain harmony and safety. In Sasak culture, the Merariq tradition serves as a conflict resolution method for addressing gender bias against Sasak women. The research underscores that Sasak women continue to fight for equal rights, and their struggle reflects the community's perspective that such rights must be earned.